Preparation method of enhanced PDMS composite material super-hydrophobic surface

By fusing glass fiber reinforced fabrics and micro-nano-inorganic particles in the polydimethylsiloxane superhydrophobic surface, the problem of insufficient mechanical tensile strength and wear resistance of superhydrophobic surfaces in the prior art is solved, and higher performance requirements and longer service life are achieved.

CN119610711APending Publication Date: 2025-03-14JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411642305.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing polydimethylsiloxane superhydrophobic surfaces have shortcomings in mechanical tensile strength and wear resistance, and it is difficult to meet the needs of multiple scenarios in practical applications.

Method used

The polydimethylsiloxane composite material that combines glass fiber reinforced fabrics and micro-nano-inorganic particles reinforced is enhanced by pouring and bubble treatment in batches, combined with the laying of glass fiber reinforced fabrics, and the tensile strength and wear resistance of the surface are enhanced.

Benefits of technology

It significantly improves the mechanical tensile strength and wear resistance of the superhydrophobic surface of polydimethylsiloxane composites, extends the service life, and achieves consistency and repeatability of performance, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119610711A_ABST
    Figure CN119610711A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrophobic surface preparation, and particularly relates to a preparation method of an enhanced PDMS composite material super-hydrophobic surface. The method comprises the following steps: preparing a basic model piece; preparing a particle enhanced PDMS (Polydimethylsiloxane) mixed solution; primary drainage pouring; at least one layer of glass fiber reinforced fabric is laid on the pouring layer subjected to bubble removal treatment; secondary dewatering and pouring; performing separation treatment on the basic model part and the composite material preformed body; and carrying out post-treatment on the composite material pre-forming body subjected to the separation treatment to form the composite material super-hydrophobic surface. According to the preparation method disclosed by the invention, on the basis of re-proportioning a PDMS solution, a special particle-enhanced PDMS mixed solution is prepared, meanwhile, secondary pouring is carried out, and at least one layer of glass fiber reinforced fabric is laid between first-layer pouring and second-layer pouring, so that the tensile strength of the super-hydrophobic surface of the prepared polydimethylsiloxane composite material is enhanced, and the super-hydrophobic surface of the polydimethylsiloxane composite material is improved. And the wear resistance is further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrophobic surface preparation, and in particular relates to a method for preparing a super-hydrophobic surface of an enhanced PDMS composite material. Background Art

[0002] Superhydrophobic surfaces play an important role in various industries and daily applications due to their excellent self-cleaning, anti-fouling, and anti-corrosion properties. However, it is usually difficult for a single material to have both good mechanical properties and superhydrophobicity. Polydimethylsiloxane (PDMS) is a flexible elastomeric material that is widely used in the fields of micro-nanotechnology, medical materials, etc. In the prior art, the superhydrophobic surface of polydimethylsiloxane has certain hydrophobicity, but its mechanical tensile strength and wear resistance cannot meet the requirements of wear resistance and mechanical tensile strength of superhydrophobic surfaces in multiple scenarios in practical applications.

[0003] During use, the existing polydimethylsiloxane super-hydrophobic surface has poor wear resistance and low mechanical tensile strength, which results in a short service life of the polydimethylsiloxane super-hydrophobic surface prepared by the existing technology. Summary of the invention

[0004] The invention aims to overcome the defects of poor wear resistance and low mechanical tensile strength of a super-hydrophobic surface of polydimethylsiloxane prepared by a preparation method in the prior art, and provides a method for preparing a super-hydrophobic surface of a polydimethylsiloxane composite material by fusing glass fiber reinforced fabric and micro-nano inorganic particles to enhance the tensile strength and wear resistance of the super-hydrophobic surface of polydimethylsiloxane.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] A method for preparing a super-hydrophobic surface of an enhanced PDMS composite material comprises the following steps:

[0007] A1. Preparing a base model, wherein the base model comprises a super-hydrophobic template or a molding mold;

[0008] A2. A particle-enhanced PDMS mixture is provided, wherein the mass ratio of PDMS prepolymer, curing agent, diluent and micro-nanoparticles in the PDMS mixture is 10:1:1 to 10:2 to 8;

[0009] A3. A hydrophobic casting is performed once, that is, the particle-enhanced PDMS mixture is cast into the base model; and the poured particle-enhanced PDMS mixture is subjected to a degassing treatment;

[0010] A4. Lay at least one layer of glass fiber reinforced fabric on the pouring layer after the bubble removal treatment;

[0011] A5. A secondary hydrophobic casting, that is, a secondary complete infiltration and coating casting of the particle-enhanced PDMS mixture prepared in step 2 is performed on a casting layer provided with glass fiber reinforced fabric; and a repair treatment is performed to prepare a composite preform;

[0012] A6. Separate the base model from the composite material preform;

[0013] A7. Post-treating the composite material preform after the release treatment to form a super-hydrophobic surface of the composite material.

[0014] Specifically, the micro-nano particles mixed in the particle-enhanced PDMS mixed solution include one or more of silicon dioxide nanoparticles, titanium dioxide nanoparticles and ferromagnetic nanoparticles; the particle size of the micro-nano particles is 30 nm to 6 μm;

[0015] The mass ratio of the micro-nano particles to the PDMS prepolymer is 2 to 8:10.

[0016] Specifically, the thickness of the glass fiber reinforced fabric in step A4 is 0.05 to 1 mm.

[0017] Specifically, if the base model comprises a super-hydrophobic template, preparing the super-hydrophobic template comprises the following steps:

[0018] A101. Select a template substrate, wherein the template substrate is made of copper or aluminum;

[0019] A102. The template substrate is textured, that is, a grating array, a dot array or a square column array pattern is textured on the surface of the template substrate using a nanosecond laser;

[0020] A103. Prepare a super-hydrophobic template, that is, use fluorosilane or stearic acid or octadecylamine or siloxane to hydrophobically treat the template substrate after the texturing treatment formed in step A102.

[0021] Specifically, the debubbling treatment of the particle-enhanced PDMS mixture uniformly cast on the super-hydrophobic template in step A3 includes the following: placing the basic model after the first hydrophobic casting in a vacuum pump for vacuum pushing bubbles; the placement time is 15 to 20 minutes.

[0022] Specifically, the repairing process for preparing the composite material preform in step A5 includes the following contents:

[0023] Smooth repair: use a blade to scrape the excess PDMS mixture poured on the glass fiber reinforced fabric for the second time;

[0024] Vacuum foaming is to place the flattened and repaired basic model part in a vacuum pump for vacuum foaming to form a bubble-free composite material preform.

[0025] Specifically, in step A6, separating the composite material preform from the super-hydrophobic template comprises the following steps:

[0026] The formed composite material preform is subjected to a curing operation;

[0027] The composite material preform after the curing operation is placed in anhydrous ethanol for ultrasonic vibration, so that the composite material preform is demoulded from the basic model part.

[0028] Specifically, if the base model comprises a super-hydrophobic template, the post-processing in step A7 comprises:

[0029] The super-hydrophobic surface of the composite material after demoulding is cleaned; that is, anhydrous ethanol is used for ultrasonic cleaning for 5 to 10 minutes;

[0030] The cleaned super-hydrophobic surface of the composite material is dried to obtain a final hydrophobic surface of the composite material.

[0031] Specifically, the basic model part adopts a molding die, and the post-processing in step A7 includes:

[0032] The obtained composite material preform is subjected to laser etching to obtain a super-hydrophobic surface of the composite material;

[0033] The obtained super-hydrophobic surface of the composite material is cleaned by using anhydrous ethanol for ultrasonic cleaning for 5 to 10 minutes;

[0034] The cleaned super-hydrophobic surface of the composite material is dried to obtain a final super-hydrophobic surface of the composite material.

[0035] Specifically, the preparation method of the particle-enhanced PDMS mixed solution comprises the following steps:

[0036] Weigh PDMS prepolymer, curing agent, diluent, and micro-nano inorganic particles in a mass ratio of 10:1:1 to 10:2 to 8;

[0037] preparing a PDMS solution, that is, mixing the weighed PDMS prepolymer and the curing agent to prepare a PDMS solution;

[0038] Micro-nano inorganic particles are added to the PDMS solution, and a diluent is added at the same time, and a magnetic stirrer is used to continuously stir at 500-600 r / min for 5-10 minutes to obtain a uniformly mixed particle-enhanced PDMS mixed solution.

[0039] The beneficial effects of the method for preparing a super-hydrophobic surface of an enhanced PDMS composite material of the present invention are:

[0040] The present invention first prepares a particle-enhanced PDMS mixed liquid, and casts the particle-enhanced PDMS mixed liquid in batches to prepare a polydimethylsiloxane composite material super-hydrophobic surface with good wear resistance and strong tensile strength. Specifically, the first casting is performed on a basic model part, and the casting layer of the first casting is subjected to a degassing treatment, and then at least one layer of glass fiber reinforced fabric is laid on the casting layer after the degassing treatment, and then the casting layer laid with the glass fiber reinforced fabric is cast for a second time, and a repair treatment is performed to prepare a composite material preform, the basic model part and the composite material preform are separated, and the composite material preform after the separation treatment is post-treated to form a composite material super-hydrophobic surface. The preparation method of the invention adds micro-nano particles to prepare a special particle-enhanced PDMS mixed solution on the basis of re-proportioning the PDMS solution, thereby increasing the properties such as wear resistance, affinity-repellency conversion, and magnetic response, and simultaneously performs secondary casting, wherein at least one layer of glass limiting cloth is laid between the first casting layer and the second casting layer, thereby enhancing the tensile strength of the super-hydrophobic surface of the prepared polydimethylsiloxane composite material and further enhancing the wear resistance.

[0041] The preparation method of the present invention can be operated in a standardized process, is easy to control, ensures the consistency and repeatability of the super-hydrophobic surface performance of the prepared polydimethylsiloxane composite material, is suitable for large-scale production, and the preparation method of the present invention does not require special equipment under special conditions to perform step processing, greatly reducing the investment in external equipment and having low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0043] Figure 1 It is a flow chart of the steps of the method for preparing the super-hydrophobic surface of the enhanced PDMS composite material of the present invention.

[0044] Figure 2 It is a schematic diagram of a method for preparing a super-hydrophobic surface according to Embodiment 1 of the present invention.

[0045] Figure 3 It is a schematic diagram of controlling the film thickness of the method for preparing a super-hydrophobic surface according to Embodiment 1 of the present invention.

[0046] Figure 4 1 is a scanning electron microscope image of the surface of a copper template according to an embodiment of the present invention.

[0047] Figure 5 3 is a scanning electron microscope image of the PDMS surface prepared in Embodiment 1 of the present invention.

[0048] Figure 6 3 is a contact angle diagram of the PDMS surface prepared in Embodiment 1 of the present invention.

[0049] Figure 7 It is a schematic diagram of a method for preparing a super-hydrophobic surface according to Embodiment 2 of the present invention.

[0050] Figure 8 3 is a scanning electron microscope image of the super-hydrophobic surface prepared in Embodiment 2 of the present invention.

[0051] Fig. 9 This is a contact angle diagram of the super-hydrophobic surface prepared in Example 2 of the present invention.

[0052] Fig.10 This is a real picture of the tensile testing machine test of the super hydrophobic surface obtained in Comparative Example 1 and Example 1.

[0053] Fig.11 This is a SEM image of the cross section of the super-hydrophobic surface obtained in Example 1.

[0054] Fig.12 It is the stress-strain curve of the PDMS super-hydrophobic surface of comparative example 1.

[0055] Fig.13 3 is a stress-strain curve diagram of the super-hydrophobic surface prepared in Example 1.

[0056] Fig.14 It is a schematic diagram of the friction and wear test of Comparative Example 2 and Example 2.

[0057] Fig.15 These are the friction and wear test results of the super hydrophobic surface obtained by Comparative Example 2 and Example 2.

[0058] Fig.16 This is the surface SEM image of the pure PDMS surface after wear test in comparative example 2.

[0059] Fig.17 This is a surface SEM image of the PDMS surface obtained in Example 2 after the wear test.

[0060] In the figure: 1. Super hydrophobic copper template 1, 2. PAMS casting layer, 3. Glass fiber reinforced fabric, 4. Blade, 5. Mold, 6. Laser, 7. Super hydrophobic surface of composite material, 8. Sandpaper, 9. Weights. DETAILED DESCRIPTION

[0061] The present invention will now be described in further detail with reference to the accompanying drawings. These drawings are simplified schematic diagrams, which only illustrate the basic structure of the present invention in a schematic manner, and therefore only show the components related to the present invention.

[0062] like Figure 1The specific embodiment of the method for preparing a super-hydrophobic surface of an enhanced PDMS composite material of the present invention shown comprises the following steps:

[0063] A1. Preparing a base model, wherein the base model comprises a super-hydrophobic template or a molding mold;

[0064] A2. A particle-enhanced PDMS mixture is provided, wherein the mass ratio of PDMS prepolymer, curing agent, diluent and micro-nanoparticles in the PDMS mixture is 10:1:1 to 10:2 to 8;

[0065] A3. A hydrophobic casting is performed once, that is, the particle-enhanced PDMS mixture is cast into the base model; and the poured particle-enhanced PDMS mixture is subjected to a degassing treatment;

[0066] A4. Laying at least one layer of glass fiber reinforced fabric 3 on top of the pouring layer 2 after the bubble removal treatment;

[0067] A5. A secondary hydrophobic casting, that is, a secondary complete infiltration and coating casting is performed using the particle-enhanced PDMS mixture prepared in step 2 on the casting layer 2 on which the glass fiber reinforced fabric 3 is laid; and a repair treatment is performed to prepare a composite material preform;

[0068] A6. Separate the base model from the composite material preform;

[0069] A7. Post-treating the composite material preform after the release treatment to form a super-hydrophobic surface of the composite material.

[0070] Specifically, the micro-nano particles mixed in the particle-enhanced PDMS mixed solution in the present embodiment include one or more of silicon dioxide nanoparticles, titanium dioxide nanoparticles and ferromagnetic nanoparticles, and the particle size of the micro-nano particles is 30nm to 6μm. Among them, the addition of silicon dioxide nanoparticles increases wear resistance, the addition of titanium dioxide particles gives the super-hydrophobic surface affinity conversion performance, and the addition of ferromagnetic powder (i.e., ferroferric oxide) particles gives the super-hydrophobic surface magnetic response performance. Silica nanoparticles, titanium dioxide nanoparticles and ferromagnetic nanoparticles can be added individually or in mixture according to specific use requirements, and there is no absolute limitation on the addition types of silicon dioxide nanoparticles, titanium dioxide nanoparticles and ferromagnetic nanoparticles.

[0071] The present invention first prepares a particle-enhanced PDMS mixed liquid, and casts the particle-enhanced PDMS mixed liquid in batches to prepare a polydimethylsiloxane composite material super-hydrophobic surface with good wear resistance and strong tensile strength. Specifically, the first casting is performed on a basic model part, and the casting layer 2 of the first casting is subjected to a degassing treatment, and then at least one layer of glass fiber reinforced fabric 3 is laid on the casting layer 2 after the degassing treatment, and then the casting layer 2 laid with the glass fiber reinforced fabric 3 is cast for a second time, and a repair treatment is performed to prepare a composite material preform, the basic model part and the composite material preform are separated, and the composite material preform after the separation treatment is post-treated to form a composite material super-hydrophobic surface. The preparation method of the invention adds micro-nano particles to prepare a special particle-enhanced PDMS mixed solution on the basis of re-proportioning the PDMS solution, thereby increasing the properties such as wear resistance, affinity-repellency conversion, and magnetic response, and simultaneously performs secondary casting, wherein at least one layer of glass limiting cloth is laid between the first casting layer and the second casting layer, thereby enhancing the tensile strength of the super-hydrophobic surface of the prepared polydimethylsiloxane composite material and further enhancing the wear resistance.

[0072] In step A2, the preparation method of the particle-enhanced PDMS mixed solution includes the following steps: weighing PDMS prepolymer, curing agent, diluent, and micro-nano inorganic particles in a mass ratio of 10:1:1 to 10:2 to 8 to prepare a PDMS solution, wherein the curing agent in the present invention uses a curing agent matching PDMS (Dow Corning 184), and the diluent uses silicone oil or n-hexane, that is, the weighed PDMS prepolymer and curing agent are mixed to prepare a PDMS solution; adding micro-nano inorganic particles to the PDMS solution, and adding a diluent at the same time, using a magnetic stirrer to continuously stir for 5 to 10 minutes at 500 to 600 r / min to obtain a uniformly mixed particle-enhanced PDMS mixed solution, wherein the particle size and type of the micro-nano inorganic particles are adjusted according to specific requirements.

[0073] In step A3, after a hydrophobic pouring, in order to ensure the excellent quality of pouring, the pouring layer 2 is subjected to a bubble removal treatment. In this embodiment, the thickness of the glass fiber reinforced fabric 3 in step A4 is 0.05 to 1 mm. Specifically, the thickness of the glass fiber reinforced fabric 3 can be 0.05 mm, 0.06 mm, 0.08 mm, 0.1 mm, etc. As a reinforcing material, the glass fiber reinforced fabric 3 can increase the mechanical properties of the polydimethylsiloxane composite material to a certain extent.

[0074] The debubbling treatment of the particle-enhanced PDMS mixture uniformly cast on the super-hydrophobic template described in step A3 includes the following: placing the basic model after a hydrophobic casting in a vacuum pump for vacuum pushing bubbles for 15 to 20 minutes. Of course, from the perspective of cost investment, the pouring layer 2 after a hydrophobic casting can be debubbled by directly placing the basic model in a room temperature for 30-45 minutes, which can also achieve the effect of debubbling the pouring layer 2.

[0075] In step A4, it is only necessary to lay at least one layer of glass fiber reinforced fabric 3 on the pouring layer 2 after the defoaming treatment at room temperature. It is only necessary to ensure that the glass fiber reinforced fabric 3 is evenly distributed on the upper surface of the pouring layer 2. No special laying environment is required, which reduces the cost investment. The specific number of layers of glass fiber reinforced fabric 3 laid is set according to specific requirements. There is no absolute limitation on the number of layers of glass fiber reinforced fabric 3 laid here.

[0076] The repairing process for preparing the composite material preform in step A5 includes the following contents:

[0077] Smoothing and repairing; that is, using a blade 4 to scrape the excess PDMS mixture poured on the glass fiber reinforced fabric 3 for the second time;

[0078] Vacuum foaming: placing the flattened and repaired basic model part in a vacuum pump for vacuum foaming to form a bubble-free composite material preform.

[0079] During the secondary hydrophobic pouring, ensure that the glass fiber reinforced fabric 3 is completely infiltrated and coated, use a blade 4 to scrape off excess mixed liquid to make the surface of the secondary pouring layer 2 smooth, and then place the basic model part in a vacuum pump for 15-20 minutes to remove vacuum bubbles to form a composite material preform.

[0080] The separation of the composite material preform from the basic model part described in step A6 includes the following steps: curing the formed composite material preform, placing the composite material preform after the curing operation in anhydrous ethanol for ultrasonic vibration, so that the composite material preform is demolded from the basic model part.

[0081] Specifically, the composite material preform is placed horizontally in an oven, heated in an environment of 40°C to 80°C for 30 to 60 minutes to slowly evaporate the solvent, and then cured at 60°C-80°C for 60 to 100 minutes to ensure that the composite material preform is completely cured. After complete curing, after the sample is cooled to room temperature (about 26°C), it is taken out of the oven and placed in anhydrous ethanol for ultrasonic vibration for 5 to 10 minutes. Due to the low surface tension of anhydrous ethanol, it is easier to enter the gap between the basic model and the PDMS, which helps to separate the basic model from the composite material preform, making the demolding process easier. After demolding, a preliminarily formed polydimethylsiloxane composite material is obtained.

[0082] It should be further explained that if the base model part includes a super-hydrophobic template, the post-processing in step A7 includes: cleaning the super-hydrophobic surface of the composite material after demolding; that is, ultrasonic cleaning with anhydrous ethanol for 5 to 10 minutes; drying the cleaned super-hydrophobic surface of the composite material to obtain the final hydrophobic surface of the composite material.

[0083] If the basic model part adopts a molding mold, the post-processing in step A7 includes: laser etching the obtained composite material preform to obtain a super-hydrophobic surface of the composite material; cleaning the obtained super-hydrophobic surface of the composite material; that is, ultrasonic cleaning with anhydrous ethanol for 5 to 10 minutes; drying the cleaned super-hydrophobic surface of the composite material to obtain the final super-hydrophobic surface of the composite material.

[0084] When the basic model part adopts a forming mold, a super-hydrophobic template is not set to set the convex and concave shapes of the super-hydrophobic surface of the two casting layers. Instead, the forming mold is used to directly perform a forming operation on the two castings, and then laser etching is performed on the composite material preform after molding to etch out a super-hydrophobic surface with a convex and concave shape (i.e., a row grating array or a point array or a square column array concave and convex structure). When selecting a molding mold, it can be selected or obtained according to the thickness requirement for the super-hydrophobic surface. It needs to be further explained that when the basic model part adopts a super-hydrophobic template, the super-hydrophobic template is used as the carrier of the first hydrophobic casting of the particle-enhanced PDMS mixture. In order to limit the super-hydrophobic surface or prevent the poured particle-enhanced PDMS mixture from overflowing the super-hydrophobic template during the two hydrophobic castings, in the process of preparing the super-hydrophobic surface of the composite material with the super-hydrophobic template, the super-hydrophobic template is first placed in a specially designed mold for molding, see Figure 3 The molding mold here may be the same as or different from the molding mold structure directly used for the above-mentioned basic model part, and may be specifically designed according to the needs of use.

[0085] Embodiment 1

[0086] The basic model in the first embodiment adopts a super hydrophobic template, such as Figure 2 As shown, a method for preparing a super-hydrophobic surface of an enhanced PDMS composite material comprises the following steps:

[0087] A1. Preparation of super hydrophobic template;

[0088] A2. A particle-enhanced PDMS mixture is provided, wherein the mass ratio of PDMS prepolymer, curing agent, diluent and micro-nanoparticles in the particle-enhanced PDMS mixture is 10:1:10:2;

[0089] A3. A hydrophobic casting is performed once, that is, the particle-enhanced PDMS mixture is cast into the base model; and the poured particle-enhanced PDMS mixture is subjected to a degassing treatment;

[0090] A4. Laying at least one layer of glass fiber reinforced fabric 3 on the upper surface of the pouring layer 2 after the bubble removal treatment;

[0091] A5. A secondary hydrophobic casting, that is, a secondary complete infiltration and coating casting is performed using the particle-enhanced PDMS mixture prepared in step 2 on the casting layer 2 on which the glass fiber reinforced fabric 3 is laid; and a repair treatment is performed to prepare a composite material preform;

[0092] A6. Separate the base model from the composite material preform;

[0093] A7. Post-treating the composite material preform after the release treatment to form a super-hydrophobic surface of the composite material.

[0094] Step A1: preparing the super hydrophobic template comprises the following steps:

[0095] A101. Select a template substrate, wherein the template substrate is made of copper or aluminum;

[0096] A102. The template substrate is textured, that is, a grating array, a dot array or a square column array pattern is textured on the surface of the template substrate using a nanosecond laser;

[0097] A103. Prepare a super hydrophobic template, that is, use fluorosilane or stearic acid or octadecylamine or siloxane to hydrophobically treat the template substrate after the texturing treatment formed in step A102. In this embodiment 1, stearic acid is used to hydrophobically treat the template substrate.

[0098] Specifically, in the first embodiment of the present invention, a periodic grating array is prepared on the surface of a copper plate by laser etching, and the copper plate with the grating array is placed in a stearic acid ethanol solution, immersed in a water bath at 70°C for 2h, and then taken out and rinsed with anhydrous ethanol, and the super-hydrophobic copper template 1 is prepared by drying. 4g PDMS and 0.4g curing agent are mixed, and a certain amount of silicone oil is added to dilute and fully stirred. At the same time, micro-nanoparticles with a particle size of 30nm are added to prepare a particle-enhanced PDMS mixed liquid, and a molding mold 5 is taken, and the super-hydrophobic copper template 1 is placed in the mold 5, and then the configured PDMS prepolymer is evenly poured on the super-hydrophobic template to ensure that its surface is completely covered with the template structure, and a layer of glass fiber reinforced fabric 3 is evenly laid on the PDMS mixed liquid to ensure that it is evenly distributed on the entire surface; a layer of PDMS mixed liquid is poured again on the laid glass fiber reinforced fabric 3 to ensure that the glass fiber reinforced fabric 3 is completely infiltrated. Figure 3 As shown, the excess PDMS mixture is removed with a blade 4 to make the surface flat, and a vacuum pump is placed in the mixture to evacuate for 30 minutes to remove bubbles. The mixture is then cured at 60°C for 4 hours, and slowly cooled to obtain a semi-finished product, i.e., a composite material preform. The obtained composite material preform is placed in ethanol and the PDMS film is carefully peeled off from the super-hydrophobic copper template 1. After drying, a super-hydrophobic surface of a polydimethylsiloxane composite material is obtained.

[0099] The super hydrophobic surface of the polydimethylsiloxane composite material prepared in Example 1 was tested by scanning electron microscopy. The results of the scanning electron microscopy test are as follows: Figure 4 and Figure 5 As shown, the surface presents a regular grating array structure, and the contact angle test results are shown in Figure 6 As shown, Figure 6 The results show that the contact angle between the super hydrophobic surface and water is 153±1.2°, which meets the super hydrophobicity requirement. The method of the invention is simple to operate and has good process controllability, and can achieve high-quality and repeatable super hydrophobic surface preparation.

[0100] Embodiment 2

[0101] like Figure 7 and Figure 8 The basic model shown uses a molding mold, and the method for preparing the super-hydrophobic surface of the enhanced PDMS composite material includes the following steps:

[0102] Mix 4g PDMS and 0.4g curing agent and stir them evenly to form a PDMS solution. Add micro-nano inorganic particles to the PDMS solution. The micro-nano inorganic particles in this Example 2 are silica nanoparticles. Add a diluent at the same time and use a magnetic stirrer to stir continuously at 500r / min for 10 minutes to obtain a uniformly mixed particle-enhanced PDMS mixture. Use a molding mold and evenly pour the configured particle-enhanced PDMS mixture into the molding mold to ensure that its surface completely covers the molding mold; lay a layer of glass fiber reinforced fabric 3 evenly on the PDMS mixture to ensure that it is evenly distributed on the entire surface, and pour another layer of PDMS mixture on the laid glass fiber reinforced fabric 3 to ensure that the glass fiber reinforced fabric 3 is completely soaked. As in Example 1 Figure 2 As shown, the excess PDMS is removed with a blade 4 to make the surface flat, and the obtained composite material preform is placed in a vacuum pump to evacuate for 50 minutes to remove bubbles, and then cured at 80°C for 3 hours. After slowly cooling, a glass fiber reinforced composite material is obtained, and the obtained composite material is fixed on the UV laser stage, as shown in FIG. Figure 7 As shown, the laser processing parameters of the nanosecond laser 6 are set, wherein the laser power is 15W, the pulse frequency is 20kHz, the scanning interval is 150um, the scanning speed is 500-600mm / s, and the processing times are 5 times. After defining the parameters, a regular square column array is etched on the surface of the composite material. The composite material after laser etching is placed in anhydrous ethanol for ultrasonic cleaning for 5 minutes to remove PDMS flying debris and residues on the surface. After taking it out, it is dried naturally or placed in a blast drying oven to complete the preparation of the super hydrophobic surface of the polydimethylsiloxane composite material. For details, see Figure 8 and Fig.11 As shown, see Fig. 9 It shows that the contact angle between the super hydrophobic surface obtained in Example 2 and water is 156±1.7°.

[0103] Comparative Example 1

[0104] Comparative Example 1 is the first pure PDMS film super-hydrophobic surface prepared by the existing template method.

[0105] like Fig.10 The mechanical properties of the pure PDMS film and the enhanced PDMS film prepared by adding in Example 1 were tested using a tensile testing machine. The test results are as follows: Fig.12 and Fig.13 As shown, from Fig.12 and Fig.13It can be clearly seen that the fracture strength of the pure PDMS film of Comparative Example 1 is 3.31MPa, while the fracture strength of the enhanced PDMS film of Example 1 prepared by the preparation method of the present invention is 58.48MPa. The results show that the present invention uses glass fiber reinforced fabric as a reinforcing material, and cross-links PDMS with glass fiber reinforced fabric by twice hydrophobic casting of particle-enhanced PDMS mixed liquid, providing extremely strong firmness and stability, and the cross-linking of PDMS with glass fiber reinforced fabric greatly increases the mechanical strength of the super hydrophobic film, giving the prepared super hydrophobic surface better practicality.

[0106] Comparative Example 2

[0107] Comparative Example 2 is a second pure PDMS film super-hydrophobic surface prepared by the existing laser etching method.

[0108] use Fig.14 The friction and wear experiment comparative example 2 shown in the figure is to test the pure PDMS hydrophobic surface prepared by the existing preparation method and the super hydrophobic surface prepared by the preparation method example 2 of the present invention, including the following steps:

[0109] First, the sample of comparative example 2 and the sample of embodiment 2 were placed on 600-1000# sandpaper 8 in sequence, and then a 400g weight 9 was applied to move 8cm in one direction, which was defined as one wear cycle. The wear condition of the sample surface coating and the change of contact angle were recorded after every 300 wear cycles. The test results are shown in Fig.15 As shown in Figure 2, the wear resistance of the super hydrophobic surface of Example 2 is better than that of the pure PDMS surface. After 1800 abrasions, the surface contact angle is still higher than 140°, showing excellent wear resistance. The surface morphology after abrasion was characterized by SEM. The SEM images of the pure PDMS and the PDMS doped with inorganic particles after abrasion tests are shown in Figure 2. Fig.16 and 17 As shown, after 1800 abrasions, the surface structure of pure PDMS was severely worn and the nanostructure almost disappeared; the square column microstructure can still be seen on the super-hydrophobic surface of PDMS prepared in Example 2, and the surface has a complex micro-nanostructure, which helps to maintain the super-hydrophobic property.

[0110] From the mechanical property test of embodiment one and comparative example one, the wear resistance experiment of embodiment two and comparative example two, it can be seen that the super-hydrophobic surface containing inorganic nanoparticles prepared by the preparation method of the present invention significantly improves the roughness of the material surface, thereby increasing the contact angle of the surface and reducing the rolling angle, and enhancing super-hydrophobic performance. The composite of glass fiber reinforced fabric and inorganic nanoparticles and PDMS can improve the mechanical strength and durability of the material, making it more stable and reliable in practical applications. And the preparation method of the present invention is through the mixing of inorganic nanoparticles and PDMS solution, and then the preparation process of the fusion with glass fiber reinforced fabric, can be realized by simple mixing, coating, curing and other processes, and is easy to prepare and process.

[0111] It should be understood that the specific embodiments described above are only used to explain the present invention, and are not used to limit the present invention. Obvious changes or modifications derived from the spirit of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a super-hydrophobic surface of an enhanced PDMS composite material, characterized in that: The following steps are involved: A1. Preparing a base model, the base model comprising a super-hydrophobic template and a molding mold; A2. A particle-enhanced PDMS mixture is provided, wherein the mass ratio of the PDMS prepolymer, the curing agent, the diluent and the micro-nanoparticles in the particle-enhanced PDMS mixture is 10:1:1 to 10:2 to 8; A3. A hydrophobic casting is performed once, that is, the particle-enhanced PDMS mixture is cast into the base model; and the cast particle-enhanced PDMS mixture is subjected to a degassing treatment; A4. Lay at least one layer of glass fiber reinforced fabric on the pouring layer after bubble removal treatment; A5. A secondary hydrophobic casting, that is, a secondary complete infiltration and coating casting of the particle-enhanced PDMS mixture prepared in step 2 is performed on a casting layer provided with glass fiber reinforced fabric; and a repair treatment is performed to prepare a composite preform; A6. Separate the base model from the composite material preform; A7. Post-treating the composite material preform after the release treatment to form a super-hydrophobic surface of the composite material.

2. The method for preparing a super-hydrophobic surface of an enhanced PDMS composite material according to claim 1, characterized in that: The micro-nano particles mixed in the particle-enhanced PDMS mixed solution include one or more of silicon dioxide nanoparticles, titanium dioxide nanoparticles and ferromagnetic nanoparticles; the particle size of the micro-nano particles is 30nm-6μm.

3. The method for preparing a super-hydrophobic surface of an enhanced PDMS composite material according to claim 1, characterized in that: The thickness of the glass fiber reinforced fabric in step A4 is 0.05 to 1 mm.

4. The method for preparing a super-hydrophobic surface of an enhanced PDMS composite material according to claim 1, characterized in that: In step A1, if the base model comprises a super-hydrophobic template, preparing the super-hydrophobic template comprises the following steps: A101. Select a template substrate, wherein the template substrate is made of copper or aluminum; A102. The template substrate is textured, that is, a grating array, a dot array or a square column array pattern is textured on the surface of the template substrate using a nanosecond laser; A103. Prepare a super-hydrophobic template, that is, use fluorosilane or stearic acid or octadecylamine or siloxane to hydrophobically treat the template substrate after the texturing treatment formed in step A102.

5. The method for preparing a super-hydrophobic surface of an enhanced PDMS composite material according to claim 1, characterized in that: The debubbling treatment of the particle-enhanced PDMS mixed solution uniformly cast on the super-hydrophobic template described in step A3 includes the following: placing the basic model after the first hydrophobic casting in a vacuum pump for vacuum pushing bubbles; the placement time is 15 to 20 minutes.

6. The method for preparing a super-hydrophobic surface of an enhanced PDMS composite material according to claim 1, characterized in that: The repairing process for preparing the composite material preform in step A5 includes the following contents: Smooth repair: use a blade to scrape the excess PDMS mixture poured on the glass fiber reinforced fabric for the second time; Vacuum foaming: placing the flattened and repaired basic model part in a vacuum pump for vacuum foaming to form a bubble-free composite material preform.

7. The method for preparing a super-hydrophobic surface of an enhanced PDMS composite material according to claim 1, characterized in that: The step A6 of separating the composite material preform from the base model comprises the following steps: The formed preform is subjected to a curing operation; The preform after the curing operation is placed in anhydrous ethanol for ultrasonic vibration, so that the preform is demoulded from the base model.

8. The method for preparing a super-hydrophobic surface of an enhanced PDMS composite material according to claim 4, characterized in that: If the base model comprises a super-hydrophobic template, the post-processing in step A7 comprises: The super-hydrophobic surface of the composite material after demoulding is cleaned; that is, anhydrous ethanol is used for ultrasonic cleaning for 5 to 10 minutes; The cleaned super-hydrophobic surface of the composite material is dried to obtain a final hydrophobic surface of the composite material.

9. The method for preparing a super-hydrophobic surface of an enhanced PDMS composite material according to claim 4, characterized in that: If the basic model part adopts a forming mold, the post-processing in step A7 includes: The obtained composite material preform is subjected to laser etching to obtain a super-hydrophobic surface of the composite material; The obtained super-hydrophobic surface of the composite material is cleaned by using anhydrous ethanol for ultrasonic cleaning for 5 to 10 minutes; The cleaned super-hydrophobic surface of the composite material is dried to obtain a final super-hydrophobic surface of the composite material.

10. The method for preparing a super-hydrophobic surface of an enhanced PDMS composite material according to claim 1, characterized in that: The preparation method of the particle-enhanced PDMS mixed solution comprises the following steps: Weigh PDMS prepolymer, curing agent, diluent, and micro-nano inorganic particles in a mass ratio of 10:1:1 to 10:2 to 8; preparing a PDMS solution, that is, mixing the weighed PDMS prepolymer and the curing agent to prepare a PDMS solution; Micro-nano inorganic particles are added to the PDMS solution, and a diluent is added at the same time, and a magnetic stirrer is used to continuously stir at 500-600 r / min for 5-10 minutes to obtain a uniformly mixed particle-enhanced PDMS mixed solution.